The Effects of Display Parameters and Devices on Spatial Ability Test Times - Tibor Guzsvinecz; Éva Orbán-Mihálykó; Cecília Sik-Lányi; Erika Perge (Applied Sciences, 2022)
The effects of display parameters and devices are examined on spatial ability test times in virtual environments. Before the investigation, completion times of 240 and 61 students were measured, using an LG desktop display and the Gear VR, respectively. The virtual environment also logged the following randomized display parameters: virtual camera type, field of view, rotation, contrast ratio, whether shadows are turned on, and the used display device. The completion times were analyzed using regression analysis methods. Except for the virtual camera type, every factor has a significant influence on the test completion times. After grouping the remaining factors into pairs, triplets, quartets, and quintets, the following can be concluded: the combination of 75° field of view, 45° camera rotation, and 3:1 contrast ratio has the largest increase in completion times with an estimate of 420.88 s—even when this combination is in-side a quartet or a quintet. Consequently, significant decreases in completion times exist up to variable quartets (the largest being −106.29 s on average), however, the significance disappears among variable quintets. The occurrences of factors were also investigated: an undefined field of view, a 0° camera rotation, the Gear VR, a 7:1 contrast ratio, and turned-on shadows are the factors that occur in most significant combinations. These are the factors that often and significantly influence completion times.